Current status and influencing factors of humanistic care in clinical nursing teaching (临床护理带教人文关怀现状及影响因素分析) - GUO Rui (郭蕊); JU Hui (琚慧); ZHAO Fan (赵璠); ZHANG Yingyu (张瀛予); LIU Wenjing (刘文静) (中西医结合护理)
Objective To understand the current status of humanistic care in clinical nursing teaching, and analyze its influencing factors. Methods Using the convenient sampling method, a total of 170 clinical nursing teachers were selected. Caring Ability Inventory and the general information questionnaire were used to investigate clinical nursing teachers. Results A total of 170 questionnaires were distributed, and 164 were effectively recovered, with an effective recovery rate of 96. 47%. The humanistic care behavior score of clinical nursing teacher was (100. 90±12. 97). Univariate analysis revealed that the dimension of respectful and connectedness was influenced by marital status, professional titles, years of working and years of clinical teaching(P＜0. 01), dimension of knowledge and skill was influenced by education level and whether having children(P＜0. 01), and dimension of assurance was influenced by marital status and whether having children(P＜0. 01). Multiple linear regression analysis showed that education level and whether having children were influencing factors of teachers’ knowledge and skill in humanistic care practice, which explained 4. 80% of the variation. Conclusion The level of humanistic care behavior in clinical nursing teacher is at a medium level, which is related to marital status. The level of humanistic care behavior in clinical nursing teacher is associated with whether having children, years of working, years of clinical teaching, professional titles, education level and other factors. Nursing managers should take targeted measures to strengthen the cultivation of humanistic care ability in clinical nursing teachers. (目的 了解临床护理带教人文关怀行为现状, 探究影响因素, 为提升临床护理人文关怀水平提供参考。方法 采用方便抽样法, 随机抽取170名临床护理带教老师为调查对象, 使用护理人文关怀量表、一般资料调查表等工具进行问卷调查。结果 共发放170份问卷, 有效回收164份, 有效回收率96. 47%, 临床护理带教人文关怀行为评分为(100. 90±12. 97)分。单因素分析显示, 尊重和联系维度与护士婚姻状况、职称、工作时长、参加带教工作时长有关(P＜0. 01), 知识和技能维度与护士文化水平、有无子女有关(P＜0. 01), 支持和保证维度与护士婚姻状况、有无子女有关(P＜0. 01)。多重线性回归分析显示, 文化水平及有无子女对护理人文关怀能力的知识和技能维度有显著影响, 可解释人文关怀能力知识和技能维度变异的4. 80%。结论 临床护理带教人文关怀行为水平处于中等水平, 与婚姻状况、有无子女、工作时长、带教时长、职称、文化水平等因素相关, 护理管理者应采取针对性的措施加强临床护理带教的人文关怀能力的培养。)